Surgical Shunting Versus Trans-Jugular Intrahepatic Portosystemic Shunt for Recurrent Variceal Bleeding in Portal Hypertension Due to Liver Cirrhosis: An Evidence-Based Case Report - Magfira, Nadya; Nurrafiani, Arie Rozzaqi; Jasirwan, Chyntia Olivia Maurine; Suhartono, Raden (The Indonesian Journal of Gastroenterology, Hepatology, and Digestive Endoscopy, 2023)
Aim: This evidence-based case report aims to determine whether the surgical shunt is better than the trans-jugular intrahepatic portosystemic shunt (TIPS) to prevent re-bleeding in patients with portal hypertension due to liver cirrhosis.  Method: Literature searching was performed in 4 online databases, Cochrane, PubMed, Embase, and SCOPUS. Three meta-analyses were appraised critically.Results: Of all meta-analyses included, the internal validities were poor and only included a small number of trials. However, the results show that surgical shunt is better for preventing variceal re-bleeding with varied heterogeneities.Conclusion: Surgical shunts may have benefits over TIPS in preventing variceal re-bleeding.